2012
DOI: 10.1080/00207594.2012.692792
|View full text |Cite
|
Sign up to set email alerts
|

Human food preferences and cultural identity: The case of Aragón (Spain)

Abstract: This research aims to analyze the relationship between sociocultural values and human food preferences. The latter, as shown in this paper, are greatly influenced by cultural identity. This work stems from a theoretical context that originated in Europe and the United States towards the mid-twentieth century, within the field of the anthropology of food. A qualitative and quantitative analysis has been performed in the Comunidad Autónoma de Aragón (Spain). Research methods include focus groups, in-depth interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Vaqué-Crusellas et al [69] state that food "includes aspects of the physical environment (where the eating takes place, the furniture, the cutlery used, sound and environmental temperature, among others), the psychosocial environment (interpersonal relationships with meal companions) and also beliefs and values held with regard to food in each socio-cultural context" (p. 964) (similar points are made by Johansson [70] and Jacobsen [16]). Cantarero et al found that people prefer to consume food that they associate symbolically with their own culture, as it reinforces their sense of belonging [71]. A multi-national study by Prescott et al [72] concluded that geographical location can be less important than common cultural values in determining food choice.…”
Section: Food Related Wellbeingmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaqué-Crusellas et al [69] state that food "includes aspects of the physical environment (where the eating takes place, the furniture, the cutlery used, sound and environmental temperature, among others), the psychosocial environment (interpersonal relationships with meal companions) and also beliefs and values held with regard to food in each socio-cultural context" (p. 964) (similar points are made by Johansson [70] and Jacobsen [16]). Cantarero et al found that people prefer to consume food that they associate symbolically with their own culture, as it reinforces their sense of belonging [71]. A multi-national study by Prescott et al [72] concluded that geographical location can be less important than common cultural values in determining food choice.…”
Section: Food Related Wellbeingmentioning
confidence: 99%
“…Food choices are driven by a combination of individual factors, social influences (networks of family and peers), physical environments (home, school, after-school programs, and neighbourhood) and macro-level environment (cultural, economic and political factors) [35,71,74,77,[80][81][82][83][84]. The term "foodscapes", originally used in geography, encapsulates these interactions well.…”
Section: Food Choices and Foodscapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers have preferred foods that were symbolically associated with their own culture, in order to reinforce their sense of belonging [39], demonstrating the power of psychological factors in motivating food behavior. Internal forces included influences such as consumers' patriotic values leading them to purchase local rather than imported foods [40].…”
Section: 'Buy Local' and Patriotic Purchasingmentioning
confidence: 99%
“…People consume foods that have a special association with their own culture to maintain ties [7]. According to Claude Lévi-Strauss, food within a society is chosen because of its meaning to the people of the society, not due to taste [8].…”
Section: Introductionmentioning
confidence: 99%